Flows of Faith
XVI, 240 p.
Keywords: Unique local transformations of the practice of established religions in Asia and the Pacific are juxtaposed with the emergence of new religious movements whose incidence is growing across the region. In Flows of Faith, the contributing authors take as their starting point questions of how religions manifest outside their cultural boundaries and provide the basis for new social identities, political movements and social transformations. With fresh insights into the globalization of beliefs, their local inflections, and their institutionalization, the authors explore how old and new religions work in different settings, and how their reception and membership challenge orthodox understandings of religion and culture. The chapters – set in Asia, the Pacific, Australia, and the US – illustrate the contrasts and commonalities of these belief systems, and their allegiances and networks in the region and beyond. They include new religious movements – Falun Gong, Brahma Kumaris, the Hare Krishna movement, based in East and South Asia with outreach posts in Australia and the U.S. – and established ‘old’ religions – Christianity, Buddhism, Hinduism and Islam – that are revitalized and recreated in different settings and places. Flows of Faith describes the transnational reaches of faith. Religious practices and their local manifestations track the movement of peoples, through mission outreach, flight, migration, and pilgrimage. In each new setting, religions are shaped by and in turn shape political and cultural forces, proving that they are resilient and generative, originary and distinctive. The volume is a major contribution, providing readers with a fresh and creative approach into the living experience of religious communities in a contemporary globalised world.